LINGUISTIC POETICS: THEORETICAL FOUNDATIONS AND APPLICATION IN LITERARY TEXTS - G’ayratova Gulzoda San’at qizi (TADQIQOTLAR, 2025)
Annotation: This article discusses the theoretical foundations of linguistic poetics, its connection with linguistics and literary studies, as well as the methods of linguistic analysis of poetic devices in literary texts. Special attention is given to metaphor, epithets, phraseological units, and syntactic devices, along with their poetic functions.